E-literary Texts: Reading Materials for School Literacy Movement - Setiyadi, D B P (KnE Social Sciences, 2018)
This research aimed to describe the efforts to provide good and appropriate e-literary texts and for reading material for the school literacy movement, and describe implementation and significance that students should obtain in relation to the mentioned objective. A qualitative descriptive method was used. The data collection techniques used were documents, in-depth interviews, and recordings. The validity of the data is checked by triangulation of data, researcher, method as well as theories. The data were analyzed using content analysis and text analysis. The result was that e-texts can be made available by searching for the materials on the Internet. The choice of e-literary texts for reading material can be done by analyzing their appropriateness in relation to the learners’ level of education. The theme of literary text content must be directed at the character building that is suitable for the school literacy movement program. The program can be applied on an ordinary level, with a 15-minute activity spent reading non-academic books before the learning time begins. The benefit for students is that they will be able to develop cultural literacy and their character building. Keywords: e-literary text, reading material, school literacy movement